Optimal Control Signal for an EEG Based Casual BCI - Sen Purkayastha, Satyajit; K Jain, V; K Sardana, H (International Journal of Engineering and Technology, 2018)
BCI (Brain computer interface) is a control and communication system which allows electrophysiological activity to control a computer or a peripheral device directly, without taking the natural route of peripheral nerves and muscles. The prime motive behind developing BCI technology was its ability to act as the only interactive link for people disabled by amyotrophic lateral sclerosis (ALS), cerebral palsy, spinal cord injury, stroke and similar neuromuscular disorders of high severity. However in the last decade, a gradual shift in BCI end-users from patients to casual (healthy) individuals has increased significantly. Because of this shift, BCI community has recognized the need for EEG based casual BCI to be more efficient and user friendly, keeping in mind the customized needs of healthy (Casual) user. So for increasing the performance of such BCIs, the selection of optimal control signal plays a very significant role. Hence, in this work, we evaluate various EEG control signals (CS) in accordance with considerations relevant to user-friendliness of casual BCIs and point up their neuro-physiological origins as well as their effectiveness in current applications. Finally, we recommend a set of parameters for selection of optimal EEG based control signal for casual BCIs and the best suitable option available among the present day control signals.Â Â Â